Heteropolyacids supported on mesoporous AlSBA-15 as efficient catalysts for esterification of levulinic acid - Lucas, Nishita; Gurrala, L.; Athawale, Anjali (Journal of Porous Materials, 2019)
A comparative study of different heteropoly acids supported on mesoporous AlSBA-15 for the synthesis of ethyl levulinate has been undertaken for the first time. The catalysts were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, inductively coupled plasma-optical emission spectrometry, thermo gravimetric analysis, temperature programmed desorption of NH3 and N-2 sorption studies. Insights into crucial parameters for the esterification reactions are also furnished. A distinct correlation was observed between acid density and conversion revealing that the distribution of acidic sites and their accessibility by the reactant moieties plays an important role in determining the overall activity. The effects of various reaction parameters were investigated to enhance the catalytic activity and yield of ethyl levulinate. Under the optimized conditions, levulinic acid conversion of 87.4 mol% and ethyl levulinate selectivity of 100% could be obtained with silicotungstic acid supported on AlSBA-15.

Unraveling the reaction mechanism of selective C9 monomeric phenols formation from lignin using Pd-Al2O3-activated biochar catalyst - Gurrala, L.; Kumar, M. M.; Yerrayya, Attada; Kandasamy, Prabu; Castano, Pedro; Raja, T.; Pilloni, Giovanni; Paek, C.; Vinu, R. (Bioresource Technology, 2022)
The conversion of biomass-derived lignin to valuable monomeric phenols at high selectivity is of paramount importance for sustainable biorefineries. In this study, a novel Pd-Al2O3 supported on activated biochar catalyst is developed for lignin hydrogenolysis. The catalyst characterization revealed that the (1 1 1) planes of both of Pd-0 and Al2O3 were exposed to the surface. The maximum lignin conversion of 70.4% along with high liquid yield (similar to 57 wt%) was obtained at 240 degrees C, 3 h and 3 MPa H-2 pressure. The total monomeric phenols yield in the liquid was 51.6 wt%, out of which C9 monomeric guaiacols constituted similar to 30.0 wt% with 38.0% selectivity to 4-propyl guaiacol. Using the reaction intermediate, coniferyl alcohol, chemoselective hydrogenation of C-alpha=C-beta is proved to occur over the Pd site, while dehydroxylation of C-gamma-OH is shown to occur over the alumina site. An impressive carbon atom economy of 60% was achieved for the production of monomeric phenols.
Keywords: Hydrogenolysis; lignin; Mechanism; Pd-Al/activated biochar; Propanol guaiacol; Propyl guaiacol